2019
DOI: 10.4103/japtr.japtr_4_19
|View full text |Cite
|
Sign up to set email alerts
|

The comparative evaluation of knowledge, attitude, and practice of different health-care professionals about the pharmacovigilance system of India

Abstract: In India, the under-reporting of adverse drug reactions (ADRs) by health professionals is recognized as one of the leading reasons of poor ADR signal detection. The knowledge of ADRs and positive attitude of health-care professionals toward ADRs reporting is vital for decreasing the irrational use of an inappropriate pharmacy. The present study was directed to assess the knowledge, attitude, and practice (KAP) of pharmacovigilance (PV) among the physicians, nurses, and pharmacists of a teaching tertiary care h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…In another study done by Bepari et al showed that higher number of the respondents do not know what to report and whom to report. 18 The present study revealed that students, interns and doctors were unaware of ADR monitoring center of their respective institution.…”
Section: Discussionmentioning
confidence: 63%
“…In another study done by Bepari et al showed that higher number of the respondents do not know what to report and whom to report. 18 The present study revealed that students, interns and doctors were unaware of ADR monitoring center of their respective institution.…”
Section: Discussionmentioning
confidence: 63%
“…All studies were published in English from 2010 to 2020. Four studies were from India [ 28 31 ], three from South Africa [ 32 34 ], three from Turkey [ 35 37 ], two from Saudi Arabia [ 38 , 39 ], two from Jordan [ 40 , 41 ], two from Pakistan [ 42 , 43 ], two from Nepal [ 44 , 45 ], one from Bhutan [ 46 ], one from Sweden [ 47 ], one from Iran [ 48 ], one from the United Arab Emirates [ 49 ], and one from Ethiopia [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three items including advising patients on possible adverse reactions, history of encountering an ADR episode with a patient, and history of ADR reporting were applied to assess nurse practice of ADR reporting. Six of the included studies in the review did not provide any information for the items applied in the practice domain [ 28 , 33 , 41 , 44 , 46 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1800 1803 024) to make drug safety information available for Indian population. Beside suspected ADR reporting form, PvPI has generated medicine side effect reporting form for consumers/patients in their regional language (Bepari et al, 2019).…”
Section: Introductionmentioning
confidence: 99%